A Retrospective Study of the Perioperative Period Management of Joint Arthroplasty in Patients with Chronic Kidney Disease. Issue 2 (1st December 2022) - Jin, Hongfu; He, Miao; Yang, Guang; Xie, Wenqing; Yu, Dengjie; Li, Hengzhen; Xiao, Wenfeng; Li, Yusheng
Abstract : Objective: With the rising prevalence of chronic kidney disease (CKD) and the increasing demand for joint arthroplasty, the management of CKD patients in the perioperative period of joint arthroplasty has become an issue worthy of attention for orthopedic surgeons. This study aimed to explore comprehensive perioperative period management strategies for CKD patients. Methods: From March 2017 to August 2022, 62 patients who underwent joint arthroplasty in our hospital were included in a retrospective study, including 31 CKD patients (mean age 69.8 ± 13.4 years old) and 31 non‐CKD patients (mean age 69.4 ± 14.2 years old). The outcome indicators were analyzed, including serum urea, serum creatinine, blood uric acid, hematocrit, and hemoglobin. Results: All patients included in the retrospective study had an average preoperative preparation time of 4.3 ± 2.6 days and an average hospitalization time of 11.0 ± 7.3 days. There were no significant differences in the changes in the serum urea values between the preoperative and postoperative measurements in the CKD patients or in the serum creatinine values and blood uric acid values ( P  > 0.05). The hemoglobin value in postoperative measurements was lower than in preoperative measurements in the CKD patients ( P  < 0.05). The hematocrit value in postoperative measurements was lower than in preoperative measurements in the CKD patients ( P  < 0.001). Conclusion: Patients with CKD have distinct characteristics compared to non‐CKD patients, and they generally have a higher risk for postoperative complications and adverse events. Recognition of risk factors, suitable timing of surgery, the undertaking of protective strategies, and proper management of complications are vital for managing CKD patients in the perioperative period of joint arthroplasty. Abstract : With the rising prevalence of chronic kidney disease and the increasing demands for joint arthroplasty, more and more chronic kidney disease (CKD) patients undergo surgical treatments to improve symptoms, enhance their quality of life, and prevent disability. However, CKD patients are in a high‐risk state during the perioperative period and the adverse event may occur postoperatively. Therefore, the management of CKD patients in the perioperative period of joint arthroplasty has become an issue worthy of attention. Those patients were of advanced age and had complex and challenging comorbidities and a high occurrence risk of adverse endings after surgery. During the perioperative period, recognition of risk factors for CKD patients can help reduce the risk of the procedure. Satisfactory renal protective strategies and graded pain management can optimize patients. Adequate preoperative preparation is the key to passing the perioperative period smoothly for CKD patients.